(untitled) - Rajan, Arvind (Hoboken, N.J., 2007)
The Structured Credit Handbook is a comprehensive introduction to all types of credit-linked financial instruments. This book provides state-of-the-art primers on single tranche collateralized debt obligations (CDOs), collateralized loan obligations (CLOs), credit derivatives (such as credit default swaps and swaptions), and iBoxx indexes. Filled with in-depth insight and expert advice, The Structured Credit Handbook covers all aspects of the synthetic arbitrage CDO market, including new instruments such as CDO2. Readers will also gain a firm understanding of the investment rationale, risks, and rewards associated with CDO investments through this valuable resource.
Keywords: Credit derivatives,Credit,Default (Finance),Nguồn tín dụng,Tín dụng,Phá sản ( tài chính ); Management,Quản trị